The night country - Albert, Melissa (Hazel Wood, 2020)
With Finch's help, Alice escaped the Hinterland and her reclusive grandmother's dark legacy. Now she and the rest of the dregs of the fairy tale world have washed up in New York City, where Alice is trying to make a new, unmagical life. But something is stalking the Hinterland's survivors--and she suspects their deaths may have a darker purpose. Meanwhile, in the winking out world of the Hinterland, Finch seeks his own adventure, and a way back home.